Multiple generalize epidermoid cysts with giant epidermoid cyst: An uncommon and rare case report (Indian Journal of Case Reports, 2025)
An epidermoid cyst (EC) is a fairly common lesion observed in young and middle-aged populations. A giant EC is described as having a size of more than 5 cm. A generalized EC involving multiple sites in the body is quite rare. Here, we present a case of a 72-year-old male presenting with a generalized EC with a giant cyst measuring 6 cm over the left knee. There was no other systemic illness. The aim of this paper was to report such a rare clinical presentation of ECs.